ANALISIS KONSEP AMAE DALAM TOKOH AISAKA TAIGA DALAM LIGHT NOVEL TORADORA KARYA TAKEMIYA YUYUKO - SAMUEL, ANDHIKA; Unsriana, S.S, M.Si, Linda (2012)
ANALISIS KONSEP AMAE DALAM TOKOH AISAKA TAIGA DALAM LIGHT NOVEL TORADORA KARYA TAKEMIYA YUYUKO -